The Effect of Changes in World Crude Oil Prices on U.S. Automobile Exports - Belenkiy, Maksim; Osborne, Stefan (International Journal of Energy Economics and Policy, 2012)
This study describes an export model where consumers differentiate between different types of automobiles by the distance they can travel on one dollar’s worth of fuel. The model predicts that the overall demand for vehicles falls as crude oil prices rise, and that the demand for less fuel-efficient vehicles falls relatively more. In particular, we estimate that between 2007 and 2008, when the crude oil prices increased by 32 percent, the export demand for the SUVs manufactured in the United States declined by over 700 million. This implies that the relatively less fuel-efficient U.S.-model vehicles will tend to suffer a competitive disadvantage worldwide when crude oil prices are high. We discuss the potential role of the proposed CAFÉ standards in improving fuel-efficiency and growing exports of the U.S. vehicle fleet. Keywords: Fuel efficiency; CAFÉ standards; International trade; Econometrics JEL Classifications: C1; F1; Q4